The Pengalaman Lelaki Seks Lelaki Terhadap Penggunaan Pre-Exposure Prophylaxis (Prep) Sebagai Upaya Pencegahan HIV : Studi Kualitatif - Lestari, Eva Dwiyanti; Herdayati, Milla (Jurnal Ners, 2025)
Human Immunodeficiency Virus (HIV) remains a significant public health issue, particularly among Men who have Sex with Men (MSM), a key population in HIV transmission. One effective prevention strategy is the use of Pre-Exposure Prophylaxis (PrEP). This study aims to explore self-perception, sexuality, and perspectives on the use of PrEP as an HIV prevention method among MSM in Tangerang Regency. This research employed a qualitative phenomenological approach and involved five key informants from the MSM community and one supporting informant from a healthcare provider. Data were collected through in-depth interviews and analyzed using thematic analysis. The results indicate that most informants experience internal conflict regarding their sexual orientation, influenced by traumatic experiences and sociocultural norms. Their sexuality is shaped not only by biological desire but also by emotional and economic factors. All informants were aware of PrEP; however, many held misconceptions about its function. Social stigma and limited access remain major barriers to PrEP utilization. Comprehensive education, inclusive health services, and community-based interventions are essential to improve the uptake of PrEP as a strategy for HIV prevention. Keywords: msm, prep, hiv prevention, qualitative study